Differential regulation of TNF receptors in maternal leukocytes is associated with severe preterm preeclampsia. (May 2015) - Minuz, Pietro; Fava, Cristiano; Hao, Shoujin; Pedraza, Paulina; Amen, Gabriella; Meneguzzi, Alessandra; Vattemi, Gaetano; Marini, Matteo; Zanconato, Giovanni; Ferreri, Nicholas R.
Abstract We tested the hypothesis that maternal peripheral blood leukocytes contribute to elevated levels of soluble TNF receptors (sTNFR) in preeclampsia (PE) with concomitant intrauterine growth restriction (IUGR). TNFR1 and TNFR2 were evaluated in a cross-sectional study comparing preeclamptic (n = 15) with or without IUGR versus normotensive pregnant women (PREG, n = 30), and non-pregnant controls (Con; n = 20). Plasma levels of sTNFR1 were higher in PE (1675.0 ± 227.1 pg/mL) compared with PREG (1035.0 ± 101.1 pg/mL) and Con (589.3 ± 82.67 pg/mL), with the highest values observed in PE with IUGR (2624.0 ± 421.4 pg/mL; n = 6). Plasma sTNFR2 was higher during pregnancy (PE: 1836.0 ± 198.7 pg/mL; PREG: 1697.0 ± 95.0 pg/mL) compared with Con (598.3 ± 82.7 pg/mL). Urinary levels of sTNFR1 and sTNFR2 were higher in PE and PREG compared with the Con group. Abundance of TNFR1 mRNA in peripheral blood leukocytes was strongly correlated with plasma levels of sTNFR1 in PE. However, TNFR2 mRNA accumulation in leukocytes did not correlate with sTNFR2 plasma levels. The level of sTNFR1 in plasma was correlated with body weight of the newborn (r = −0.56). The data suggest that maternal leukocytes contribute to sTNFR1 levels in plasma in association with decreasing newborn weight and PE with concomitant IUGR.